The Risk Analysis of Musculoskeletal Disorders in Pottery Making Workers in Kasongan, Bantul - Caesar Zainur Barik; Liena Sofiana (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Musculoskeletal problems are problematic in Indonesia because manual work activities such as lifting, transporting, pulling and pushing are still being done. Pottery-making workers in the Kasongan are still doing those moves traditionally such as lifting, transporting, pulling and pushing manually. The purpose of this study was to analyze the risk of MSDs in the pottery making workers in Kasongan. This research was cross sectional design. The sample amounted to 78 workers selected using accidental sampling techniques. The instruments used Nordic Body Map questionnaire and Rapid Entire Body Assessment. Data analysis was using the chi fisher test. The results showed that the variables associated were age (sig= 0.000) and variables that had no relationship were gender (sig= 0.341) and work posture (sig= 0.352). The risk factor associated with complaints of MSDs is age, so to reduce the risk of the occurrence of MSDs, they can do physical activity or stretch muscles.